Argon Laser Peripheral Iridoplasty and Argon Laser Pupilloplasty: Alternative Management for Medically Unresponsive Acute Primary Angle Closure - Wenkai Zhou; Fangkun Zhao; Dong Shi; Majida Qadri; Lingfeng Jiang; Liwei Ma (Journal of Ophthalmology)
Objective. To introduce the combined laser technique, argon laser peripheral iridoplasty (ALPI) and argon laser pupilloplasty (ALPP), in the management of medically unresponsive acute primary angle closure (APAC). Design. Retrospective study. Methods. We retrospectively reviewed the records of 23 patients (27 eyes) with APAC, who were applied ALPI and ALPP when traditional treatment failed. The visual acuity and intraocular pressure (IOP) were monitored before surgery and at 1, 2, 12, 24, and 48 h after surgery. Additionally, the angle-opening status was monitored before surgery and 48 h after the treatment by using an ultrasonic biological microscope (UBM), and the presurgical and postsurgical cornea edema statuses were observed by using a slit lamp. We also documented the complications of laser treatment. Results. For the ALPI + ALPP laser-effective group, the presurgical IOP was 52.1 ± 9.3 mmHg and the postsurgical IOP was 37.6 ± 10.9 mmHg (1 h), 28.4 ± 12.4 mmHg (2 h), 19.9 ± 9.0 mmHg (6 h), 16.8 ± 7.3 mmHg (12 h), 15.9 ± 5.9 mmHg (24 h), and 14.9 ± 5.0 mmHg (48 h), with statistically significant differences (p<0.05) in each time point. It was observed in all the patients that the corneal edema alleviated, the angles opened, and visual acuity recovered with varying degrees at 48 h after applying combined laser treatment. For the ALPI + ALPP laser-ineffective group, further interventions were taken. Definite treatment was given in both groups to maintain the long-term IOP control. Conclusions. Although the combination of ALPI and ALPP is a temporizing therapeutic strategy for APAC, it is effective in relieving pupillary block which is unresponsive to miotic agents, opening the closed angle to a certain extent, restoring the transparency of cornea, and reducing IOP to a safe level for further definitive treatment.